On Frames in Banach Spaces - Vashisht, L. K. (Communications in Mathematics and Applications, 2012)
Banach frames of type ω P^*, shrinking Banach frames and retro shrinking Banach frames in Banach spaces have been introduced and studied. Necessary and sufficient conditions for a Banach frame (retro shrinking Banach frame) to be shrinking are given. Relation between various types of Banach frames are discussed.